Bending strenght properties of small clear specimen from Merawan and Keruing / Noor Azrieda Abd Rashid - Abd Rashid, Noor Azrieda (2004)
Solid wood is important material that use in construction and interior uses. This research is to determine the Modulus Of Rupture (MOR) and The Modulus Of Elasticity (MOE) of small clear specimen from Merawan (Hopea spp) and Keruing (Dipterocarpus spp) species. This research were using the bending test to determine the value of (MOR) and (MOE). From this study, show Merawan species not suitable for the external uses compared to Kerning although, from the same strength group. Although not all the testing that were carried out not pass the standard (BS 373: 1957), nevertheless in general know the various product will be provide from Merawan and Keruing in wood industrial sector. In conclusion, Merawan and Kerning have a high quality potential if have a good treatment before use it for the specific purpose.